Answer:
x = 6
Explanation:
3x - 3= 27 - 2x
First we put all the x terms to on side, making it 3x + 2x - 3= 27.
Remeber that when we move a term to the other side of the equals sign (=), we change its sign to be the opposite of what it currently is.
Then, we move all the numberics to the other side, so we derieve 3x + 2x = 27 +3. Again, the sign changes when we move it across.
What is left to do is add up the quantities. So 3x + 2x = 5x and 27 +3 = 30.
We are left with 5x = 30. If 5 x's is 30, how much is one? Sinply divide it to get the answer of 30 / 5 which is six!
To make sure the answer is correct substituite 6 in the equation as x and see if its accurate: 3(6) -3 = 7 - 2 (6). And it is!
So x is equal to six.